기록관리 대상으로서 SNS 연구 - 송주형; Song, Zoo-Hyung (기록학연구, 2014)
This study examined the influence and meaning of SNS as the hot topic of our time from the archival perspective and also studied the 'SNS records management'. The many users mean a high accessibility and utilization of SNS, which increase the influence and value of SNS as a record. Politically, SNS is a tool that strengthens the communication among the voters, politicians and the public while economically, it is a window to accept the complaints of the customers and a marketing tool. In addition, the voices of social minorities are also recorded unlike in the traditional media, which makes the SNS record a method to gain the social variety and diversity. SNS is a place of formation of collective memory and collective memory itself. Furthermore, it can play the role of public sphere. It also is a place for generation of 'big data' in an archival sense. In addition, this study has classified the SNS records management into primary and secondary management that include record management entities, subjects, periods, methods, and causes. This study analyzed the history, status, and the meaning of SNS to assess the values and meanings as the preliminary study for the future SNS record management studies. 본 논문은 우리 시대의 화두라 할 수 있는 SNS의 영향력과 의미를 기록학적 측면에서 살펴보고 'SNS 기록관리'의 필요성을 역설했다. 기존 연구에서 SNS는 주로 홍보를 위한 도구적 성격이 강조 되었다. 하지만 SNS 사용인구가 증가하면서 기록으로서의 SNS 영향력과 가치가 증대되고 있다. 정치적으로 SNS는 유권자와 정치인 간의 소통을 강화하는 도구이며, 경제적으로 SNS는 기업에 대한 고객의 불만을 접수하는 창구이자 마케팅 도구이다. 또한 기존 미디어에서 소외되었던 상대적 약자들의 목소리가 기록된다는 면에서 SNS 기록은 사회적 다양성 확보의 수단이자 다양성 그 자체이다. SNS는 집단 기억 형성의 장이자 집단기억 그 자체이며, 공론장의 역할을 수행할 수 있다. 빅데이터 형성의 장이자 빅데이터 그 자체로서의 SNS 또한 기록학적 의미를 지닌다. 인류 역사는 매체의 역사라 볼 수 있는 만큼 SNS 그 자체도 기록되어야 하며 SNS의 휘발성 또한 SNS를 기록으로 관리해야하는 의미를 가지고 있다고 볼 수 있다. 또한 본 논문은 SNS 기록관리를 1차적 관리와 2차적 관리로 나누어 각각 기록관리 주체와 대상, 시기, 방법, 이유 등의 원칙을 구분해 보았다. 1차적 관리는 당사자가 실시간으로 웹에서 무차별적, 시스템적으로 이뤄져야 하며, 2차적 관리는 전문가나 위원회 등에 의해 티핑포인트에서 다양한 평가와 선별을 거쳐, 사회적 문화적으로 수행돼야 한다고 제안했다. 본 논문은 SNS의 역사와 현황, 각종 사례를 분석해 그 가치와 의미를 살펴보고 있으며, 이는 앞으로 이뤄져야 할 SNS 기록관리 연구를 위한 서론 또는 총론의 성격을 지닌다고 할 수 있다.